2001
DOI: 10.1002/cne.1338
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and circadian variation of protein kinase C immunoreactivity in the rat retina

Abstract: We studied the dependence of the expression of protein kinase C immunoreactivity (PKC-IR) in the rat retina on the light:dark (LD) cycle and on circadian rhythmicity in complete darkness (DD). Two anti-PKC alpha antibodies were employed: One, which we call PKCαβ recognized the hinge region; the other, here termed PKCα, recognized the regulatory region of the molecule. Western blots showed that both anti-PKC antibodies stained an identical single band at approximately 80 kD. The retinal neurons showing PKC-IR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 43 publications
8
31
2
1
Order By: Relevance
“…In accordance with previous studies [Greferath et al, 1990;Gabriel et al, 2001], protein kinase Cα (PKCα) immunoreactivity is mainly localized in rod bipolar cells (Fig. 6).…”
Section: Cells Of the Adult Elephant Retinasupporting
confidence: 72%
See 1 more Smart Citation
“…In accordance with previous studies [Greferath et al, 1990;Gabriel et al, 2001], protein kinase Cα (PKCα) immunoreactivity is mainly localized in rod bipolar cells (Fig. 6).…”
Section: Cells Of the Adult Elephant Retinasupporting
confidence: 72%
“…In addition to rod bipolars, PKCα is also expressed by a subpopulation of amacrine cells (Fig. 6), as previously observed in the rodent retina [Gabriel et al, 2001;Iandiev et al, 2007]. The somata of PKCα-expressing bipolar cells lie in the outer half of the INL; short (Fig.…”
Section: Cells Of the Adult Elephant Retinasupporting
confidence: 48%
“…Xu et al (2003) showed with use of the Alomone ␣1C antibody that the immunostaining appeared not as puncta, but rather was smooth, particularly in rod bipolar cells and in dopaminergic amacrines and some other amacrine neurons of unidentified subtype. The staining pattern and the reactive cells were remarkably like what has been reported for PKC␣ immunostaining in rat retina (Gabriel et al, 2001). Using the anti-␣1C antibody developed by McRory et al (2004), however, we observed that whether the immunostaining was smooth or punctate was a function of concentration and location.…”
Section: ␣1bsupporting
confidence: 56%
“…Circadian rhythms have been also reported for the levels of mRNA encoding rod and cone photopigments (von Schantz et al 1999), for protein kinase C immunoreactivity (Gabriel et al 2001), and for GABA turnover rate and release (Jaliffa et al 2000). have demonstrated that, in the rat retina, the levels of several amino acid show a daily rhythm.…”
Section: Circadian Rhythms In the Retinamentioning
confidence: 93%